Assessment of spatial and seasonal changes in groundwater nitrate pollution of agricultural lands through ordinary and indicator kriging techniques. Issue 7 (7th June 2017) - Arslan, Hakan; Ayyıldız Turan, Nazlı; Demir, Yusuf; Güngör, Alper; Cemek, Bilal
ABSTRACT: Geostatistical approaches (ordinary kriging (OK) and indicator kriging (IK)) were used in this study to investigate the spatial and temporal variations in groundwater nitrate concentrations in Çarşamba plain of Turkey. Groundwater samples were taken in April 2012, July 2012, September 2012 and March 2013 from 78 groundwater wells. The experimental semivariograms were often fitted well by a Gauss model for April 2012 and September 2012, whereas a spherical model was fitted to experimental semivariograms for July 2012 and March 2013. Spatial distribution maps revealed that groundwater nitrate concentrations were above the threshold value of 50 mg L −1 specified for drinking water in 4.3% of the study area in April 2012, 40.8% in July 2012, 32.8% in September 2012 and 19.1% in March 2013. Probability maps created with IK showed that 3.1% and 3.2% of the total area had very strong probability (0.8–1.0) of exceeding the threshold nitrate concentration in July 2012 and September 2012, respectively. Current findings revealed that groundwater nitrate concentrations changed seasonally and increased much more in summer. It was concluded that OK and IK may yield significant outcomes for groundwater management, identification of risky sites for potential pollution and identification of the sites with excessive fertilizer uses.